Avaliação de componentes informacionais de etiquetas de roupas: o caso de etiquetas de roupas infantis de 0 a 7 anos em São Luís – MA - Nunes, Tatiana Barros de Oliveira (2016)
This thesis aims to analyze the information contained in 0-7 years old children’s clothing labels found in large shopping centers from São Luís - MA. It took into account the understanding of the information and graphic symbols presented on the labels by the indirect consumers of children's clothing products, based on the ABNT standards (NBR 16365: 2015), related to the security of children's clothing – fixed cords specifications and adjustable cords on children's clothing and haberdashery in general - physical risks. This research is characterized by an applied nature, with a qualitative approach and descriptive purpose, being divided into three phases. In phase 1, there was a survey of labels in large shopping centers in São Luís. In phase 2, the informational content and graphic symbols of the labels were analyzed, considering the variables of NBR 16365:2015 and ISO 3758:2013 for textiles, which specifies care codes using symbols, in addition to analysis based on the warning variables presented by Wogalter, Desaulniers and Godfrey (1985). In phase 3, questionnaires were administered among indirect consumers to check their behavior on the information found on the labels. From the results found it is possible to affirm that among the analyzed labels, in general, the information was not presented according to NBR 16365:2015 and it was not detected information related to the variables of Wogalter, Desaulniers and Godfrey (1985). Regarding to the ISO 3758:2013, only a small portion of the labels was in accordance with its recommendations. It is noteworthy that the indirect consumers of infant clothing are unaware of the NBR 16365:2015, which consequently can expose children to potential risks during the use of clothes. It was noted, also, that from the little understanding of the information contained in children's clothing labels, the indirect consumer recognizes the importance and the need for information regarding security on labels affixed to clothing.